Simulation of a robotic bird - Couceiro, Micael S. (2008)
In this paper it is studied the dynamics of the robotic bird. The system performances are analyzed in terms of time response and robustness. It is study the relation between the angle of attack and the velocity of the bird, the tail influence, the gliding flight and the flapping flight. In this model, a bird flies by the wind beat motion or using its tail down. The results are positive for the construction of flying robots. The development of computational simulation based on the dynamic of the robotic bird that should allow testing strategies and algorithms of control.